Overview of production and tendency on halal products and services in Malaysia and global market / Mohamad Idham Md Razak … [et al.] - Md Razak, Mohamad Idham; Omar, Roaimah; Talib, Adi Hakim; Semil@Ismail, Ghazali; Jafri, Fakrulnizam (Division of Research and Industry Linkages, UiTM Melaka, 2014)
This study embarked on the importance and tendency on Halal products and services in-Malaysiaand-Global-Market.-In-global-market,-consumcr-basc-for-Halal-products is around 1.7 billion people and worth more than 2.3 trillion dollars. It makes the Halal market vitally important emerging sector that should not be overlooked. From the market perspective, traditional target market remains in Asia and Middle East, however due to the effect of globalization, there is a significant development of market size for Halal market in Europe and USA. Besides in Western country, most Halal product is still not readily available for UK market. We see this phenomena being applied not only on food items. Personal hygiene and healthcare products, toiletries and cosmetics are all appearing as Halal options. Once Halal is understood as a lifestyle choice, the range of options for Halal product will increase exponentially. In Malaysia, Halal products is not a big issue as we can find Halal food everywhere from the street market up to the high-end chain. The competition can be considered intense in the market.